2002
DOI: 10.1159/000065290
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profiles and Outcomes of End-Stage Renal Failure Patients with Late Initiation of Renal Replacement Therapy Based on Uremic Symptoms under Intensive Renoprotective Therapies

Abstract: Aim: This study describes the clinical profiles and outcomes of renal failure patients with late initiation of renal replacement therapies (RRT) based on uremic symptoms under intensive treatment prior to the start of RRT (IT). Methods: Thirteen patients (male 10, female 3) with end-stage renal disease who preferred to wait for the initiation of RRT until uremic symptoms appeared regardless of serum creatinine (s-Cr) and 24-hour creatinine clearance (24-hour Ccr) were chosen. All patients received IT including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Therefore, patients with advanced CKD typically retain phosphate and develop hyperphosphatemia. Previous research indicated that significant hyperphosphatemia occurred in CKD patients who were under intensive treatment and who chose to delay initiation of RRT [14] . However, it is unknown if hyperphosphatemia can be used as an indicator for initiation of RRT in such patients.…”
mentioning
confidence: 99%
“…Therefore, patients with advanced CKD typically retain phosphate and develop hyperphosphatemia. Previous research indicated that significant hyperphosphatemia occurred in CKD patients who were under intensive treatment and who chose to delay initiation of RRT [14] . However, it is unknown if hyperphosphatemia can be used as an indicator for initiation of RRT in such patients.…”
mentioning
confidence: 99%